Coevolution and the adaptive value of autumn tree colours: colour preference and growth rates of a southern beech aphid - Ramírez, C; Lavandero, B; Archetti, M (Blackwell Publishing, 2008)
The evolutionary explanation for the change in leaf colour during autumn is still debated. Autumn colours could be a signal of defensive commitment towards insects (coevolution) or an adaptation against physical damage due to light at low temperatures (photoprotection). These two hypotheses have different predictions: under the coevolution hypothesis, insects should not prefer red leaves in autumn and grown better in spring on trees with green autumn leaves. Under the photoprotection hypothesis insects should prefer and grow better on trees with red leaves because they provide better nutrition. Studying colour preference in autumn and growth rates in spring of a southern beech aphid species (Neuquenaphis staryi) on Nothofagus alessandrii we found preference for green leaves in autumn but not differential performance of aphids in spring. We suggest that aphid preference for green might have evolved to exploit better their host during the autumn rather than to improve their performance in spring.